Comparison of Serum Glutamic Pyruvic Transaminase and Serum Glutamic Oxaloacetic Transaminase Enzyme Levels between Light and Heavy Drinkers in Renon Village, Denpasar City - Ni Putu Rahayu Artini; I Wayan Tanjung Aryasa (Jurnal Penelitian Pendidikan IPA, 2023)
Arak is a non-electrolyte liquid that easily circulates in the blood circulation and is absorbed in the digestive tract. One disease that can be caused by alcohol consumption is liver function disorders, such as alcoholic hepatitis. So it can increase the serum enzymes glutamate pyruvate transaminase (SGPT) and serum glutamic oxaloacetic transaminase (SGOT). This research was conducted on light and heavy drinkers in Renon Village, Denpasar City. This research uses a longitudinal quantitative design. The results obtained were that the average SGPT level of light drinkers was 46.21 ± 0.155 IU/L, while the respondents who were heavy drinkers had SGPT levels with an average of 64.02 ± 0.430 IU/L. for SGOT from light drinkers is 50.20 ± 0.101 IU/L. Respondents who drank heavily had SGPT levels with an average of 74.40 ± 0.048 IU/L. All wine drinkers, both light drinkers and heavy drinkers, had SGPT-SGOT levels that exceeded the reference value.